Identifying Transformations in Labor and Production among Industrial Zone Workers in the Context of the Fourth Industrial Revolution - Huyen Trang, Vu; Thi Quynh Trang, Vu; Thi Quynh Anh, Nguyen (VNU Journal of Science: Policy and Management Studies, 2025)
The Fourth Industrial Revolution has generated profound transformations in labor and production across Vietnam’s industrial zones, particularly affecting the industrial workforce. The increasing integration of technologies such as automation, artificial intelligence, and the digitalization of production processes has reshaped job structures, skill requirements, and workers’ lifestyles. This paper analyzes several concrete manifestations of these transformations, including changes in work content and format, employment conditions, supplementary income activities, and the impacts on workers’ health, personal lives, and adaptive capacities. These changes reflect the emergence of a new labor model in the digital age, where workers are simultaneously confronted with heightened demands for skills and performance, while also encountering opportunities to develop in more flexible, diverse, and technology-driven directions. These dynamics, in turn, call for the effective governance of lifestyle transformations among industrial workers to ensure a balanced integration of technological adaptation and social stability within modern industrial zones.